Aprender, viver e sentir a terra : subsídios para a educação ambiental - Giron, Heloísa (2019)
The present research was developed with the intention of resembling the act of sowing. The sowing takes place in the relationship between the earth and the human action of the sowers, mediated by work and seeds. The fertile land that nurtured and supported the research was the Nova Estrela Settlement, located in the municipality of Vacaria, Rio Grande do Sul and the Chico Mendes State School of Elementary Education, which operates on its lands. The seeders of the process were the teachers, students and their families and the researcher. The general objective of the research was to understand what the perceptions about environmental education are practiced in a rural school inserted in a rural settlement. For the specific objectives, the proposal was to identify the environmental perceptions presented by the school community - teachers, students and family members - and to investigate how the pedagogical team perceives the environmental education practices they develop. The writing option was the narrative, aiming to present the knowledge as subordinate to the place where it is conceived. The sowing or the work, was in practices of environmental education developed in the school with the students and teachers. In order to account for the proposed objectives, conceived activities were grouped in “strength verbs”. Problematization aimed to understand how students perceived the earth as a representation of the environment. Raising awareness had as its goal promote self-recognition of students as part of a collectively group of resistance. Listening to neighbors and family members aimed to promote students identification with them as producers of knowledge and culture. Sharing reflections and ideas as a way to bring the community closer to the school. The germinated seeds from sowing process were the ideas that emerged from the practice. Ideas that work as subsidies for environmental education. They are: the rooting of the subjectivities in the organic and the cultural background they are into, having as one of its means of manifestation the work; and the search for an attitude of care in human’s life, in the sense of bringing it closer to its fundamental way of being.